Analisis Efektivitas Alur Logistik Inbound dan Strategi Alokasi Persediaan Omnichannel (Online & Offline) di Heybeb Factory Outlet - Muslimah, Putri Restoening (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
In the fast-moving fashion retail industry, supply chain efficiency is a key factor in operational success. Heybeb Factory Outlet, as one of the retail business actors, faces challenges in managing the flow of goods from upstream to downstream, particularly in balancing demand between offline (physical stores) and online (e-commerce/marketplace) channels. This proposal aims to design and analyze the logistics workflow starting from goods ordering (restocking) from the central warehouse, the goods receiving process, rigorous Quality Control (QC) procedures, storage in a dedicated transit warehouse, and the stock distribution mechanism (stock split) for the two sales channels. The main issues identified include the risk of overselling in one channel while stock accumulation occurs in another, as well as the potential for defective items to pass through due to an unstructured QC process. This study employs a descriptive qualitative approach by mapping out an ideal Standard Operating Procedure (SOP). The expected outcome is the development of an integrated inventory management system capable of minimizing return rates caused by defective items and maximizing inventory turnover through accurate stock allocation between online and offline divisions.